A Better Posture Strategy for Fingertip Force and Finger Coordination during a Daily Activity. (28th April 2014) - Huang, Chen‐Yu; Su, Fong‐Chin
<x xml:space="preserve">Abstract</x> An effective jar opening movement requires not only the complex integration of the thumb and fingers but also good body segment coordination dependent on the body posture. However, few studies have focused on the effect that jar opening posture has on the finger force integration when the fingertips are grasping the jar in their natural positions, rather than fixed ones, and few have considered the role of the global motor in this task. Forty‐two healthy young subjects participated in this study and performed the jar opening movement using a custom instrument with three opening postures. The results showed that the resultant force and overall torque of the right hand significantly increased from the vertical to the off‐table posture. The thumb produced the greatest resultant, tangential and normal forces when the off‐table posture was used. Further, the average normalized normal forces of the thumb and middle–ring–little finger group were greater for the off‐table posture than those for the vertical posture, whereas no difference was found for the index finger. The normal forces were 3.02–3.36 times greater than the tangential forces for the three finger groups. The thumb had the greatest torque contribution and produced the same torque contributions for all the three postures. The torque contributions of the index finger and the middle–ring–little finger group were 0.56–0.96 times smaller than that of the thumb. This study found a better posture strategy for the young subjects to open a jar with the off‐table posture while sitting, and this was also the best opening posture when comparing the overall torque in this work with that reported in previous studies, no matter whether the subjects were standing or sitting or whatever type of finger group was defined. However, the effect of grasp type and the middle, ring and little fingertip force need to be clarified in future studies. Copyright © 2014 John Wiley & Sons, Ltd.